THE BENCHMARK ANALYSIS OF TOURISM IN ROMANIA AND JAPAN - Georgiana BADICU; Iancu DORIN (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
In the last decades, the tourism developed a lot, especially due to technological advances and access to an ever-increasing range of means of transport that allow convenient and fast travel over long distances and their increasingly affordable costs. Tourism is an important factor in both promoting countries and cultures, as well as in the economy. Every culture is unique and an effective strategy to attract tourists can benefit both in the country's economy and in creating a diverse population. Benchmarking is a valuable tool for managing companies, local governments, governments in their development strategies. Companies, settlements, regions, states, governments that compare their performance with others and identify best practices get strategic, operational and economic benefits, leading to increased competitiveness. Thus, this paper proposes comparative analysis by benchmarking of four categories of aspect related to tourism in Romania and Japan: Tourist Indicators, Human Resources in Tourism, Business Environment, and Competitiveness of Tourism Prices.